ANALISIS YURIDIS WANPRESTASI DALAM KASUS JUAL BELI MATERIAL BESI DAN SENG: Juridical Analysis of Breach of Contract in the Case of Sale and Purchase of Iron and Zinc Materials - Ajie Dharmaputra; Sri Bakti Yunari (Reformasi Hukum Trisakti, 2024)
The sale and purchase agreement that ended in a lawsuit for breach of contract occurred because one of the parties did not fulfill its obligations. The problem in this paper is the implementation of agreement between PT AS and PT HM reviewed from the applicable provisions and the method of resolving the breach of contract in court. For the finding results and conclusion in this case, PN Tangerang won PT HM, while PT Banten won PT AS. The Supreme Court confirmed the decision of PT Banten. Obtained is that the agreement is valid and binding even though it was not made in writing. In its implementation, PT AS has fulfilled its duty, while PT HM has not fulfilled its duty or is in breach of contract. The type of breach of contract committed by PT HM is carrying out what was promised, but not completed. The action of PT HM in refusing to comply with court decision and submitting a PK using falsified evidence shows that PT HM has violated the principle of good faith and can be charged with a civil lawsuit (PMH) and a criminal lawsuit (fraud / embezzlement / default and falsification of documents).